The Role of Alkylammonium Bromides on the Surface Passivation of Stable Alcohol-Dispersed CsPbX3 Nanocrystals and on the Stability Enhancement in Light-Emitting Applications - Uribe-Vegas, Pablo; Villanueva-Antoli, Alexis; Segura, Camilo; Werlinger, Francisca; Aliaga, Karen R; Caprile, Renato; Trofymchuk, Oleksandra S; Flores, Mario E; Osorio-Roman, Igor O; Echeverria-Arrondo, Carlos; Das Adhikari, Samrat; Selmi, Olfa; et al. (Wiley-VCH, 2024)
The ligand passivation is considered an attractive strategy to prepare high-quality perovskite nanocrystals (PNCs) with improved photophysical features in polar media. However, the long-term stabilization of PNCs in these environments is still challenging, being pivotal to understanding the protection mechanism given by prominent surface ligands and avoiding material deterioration in polar solvents. In this work, how the nature of diverse alkylammonium bromides used during surface passivation influences the photophysical properties and quality of CsPbX3 PNCs fully dispersed in alcohol environments, exhibiting stability up to 10 months are investigated. By adding didodecyldimethylammonium benzyldodecyldimethylammonium and tetrabutylammonium bromides (DDAB, BDAB, and TBAB, respectively), DDAB and BDAB promote a suitable and partial surface coverage are observed, respectively, suppressing defect sites in the nanocrystals. Conversely, TBAB shows poor surface protection, decreasing the PL features of PNCs. The presence of DDAB and BDAB favors the fabrication of color converters, and efficient light-emitting diodes (LEDs) with external quantum efficiencies (EQE) of approximate to 23%. Interestingly, significant device stability with BDAB capping shows an LED half-life of 20-fold longer than for DDAB. This contribution offers a promising approach for preparing highly luminescent and stable alcohol-dispersed PNCs, useful for fabricating efficient optoelectronic devices.
Role alkylamoniumbromidů na povrchovou pasivaci stabilních nanokrystalů CsPbX3 dispergovaných v alkoholu a na zvýšení stability v aplikacích emitujících světlo
Keywords: alcohol-stable nanocrystals; color converters; light-emtting diodes; surface passivation; steric hindrance; nanokrystaly stabilní v alkoholu; převodníky barev; diody vyzařující světlo; povrchová pasivace; stérická zábrana